Pengaruh Komitmen Organisasi, Penghargaan dan Kepuasan Kerja Terhadap Perputaran Karyawan Pada Perbankan Syariah di Kota BATAM - Ahmad Zulva Adi; Sri Langgeng Ratnasari (ETIKONOMI, 2015)
The Effect of Organization Commitment, Reward, and Work Satisfaction to Turnover in Islamic Banking at BatamThis study aims to analyze the effect of organizational commitment, reward to turn-over intention through work satisfaction variable and to analyze the most affective variable on turn-over intention. The method that used on this study is path analysis. According to the analysis, it is concluded as the followings: organizational commitment has effect on work satisfaction, reward  has effect on work satisfaction, work satisfaction has effect on turnover intention, organizational commitment has a effect on turnover intention, reward has a effect on turnover intention, organizational commitment has a effect on turnover intention through work satisfaction, reward has a effect on turnover intention through work satisfaction.DOI: 10.15408/etk.v14i1.2262